No one is left behind in the fight of the EU against violent extremism - Deborah Phares (Freedom from Fear, 2020)
31st January 2019, at the European Parliament in Brussels, several officials, experts, researchers and journalists concerned with finding solutions to the rise of violent extremism in the Maghreb and Sahel region gathered to share insights on a 5 million euros European Union (EU) funded programme implemented by UNICRI.